A trajetória do portador de sofrimento psíquico no processo de desinstitucionalização: história oral - Silva, Priscilla Maria de Castro (2012)
The Psychiatric Reform Law 10.216/2001, created the conditions for the gradual replacement of asylums and as a result opened the possibility of breaking away from the hospital-hegemonic model, a model for community-based. And, as the bearer of mental suffering will be rehabilitated, new structures must emerge to compose your support network, and support in their process of Deinstitutionalization and Social Inclusion. This study aimed to know the trajectory of the carrier of the mental suffering in the deinstitutionalization process, considering the process of rehabilitation and social inclusion. This is a comprehensive study - interpretative and qualitative, based on the assumptions of Oral History, proposed by Bom Meihy. Was conducted with ten users that they were in a CAPS in Campina Grande / PB / Brazil and that were in the process of rehabilitation and social inclusion. The empirical material was produced in the period from June to July 2012, and followed all the steps of production of empirical material proposed by Bom Meihy. The empirical material was discussed in light of the interpretive thematic analysis technique proposed by Minayo, which resulted in a large main theme entitled: Trajectories of life: the overcoming of prejudice to strengthening the resilience and three sub-themes: From House to Psychiatric Services ; The CAPS family, school and work ; Looking for a new social place: Possibilities and difficulties . The results revealed stories of pain, abuse, violence, poverty, abandonment, contributing to the onset of seizures, and subsequent demand for specialized services. Prejudice was one of the most difficult obstacles to be faced by the employees, and the narratives demonstrate great faith, resilience, empowerment and overcoming this prejudice and social stigma. The discovery of CAPS as a place of support, care and rehabilitation, promoted the construction of a network of support and provided intersectorality as numerous agencies that favor the inclusion of such persons in the labor market, school and various social environments. However, CAPS has become an ambiguous environment with respect to inclusion through work, for he had produced, could not be marketed within the craft service, which denoted an inability of professionals to act in this sphere CAPS care. A strategy that employees used to reenter the job market, was the omission of one day were treated in CAPS, dodging the stigma they received when they started dealing in a Mental Health service. One obstacle was revealed a lack of financial development for diverse social inclusion initiatives, but in this research, was appointed the solidarity economy, which provided increased autonomy of the individuals involved, and created spaces for a decentralized and participatory management. And as more favorable finding of this investigation was the possibility of deinstitutionalization in the broad sense. Some strategies necessary such as strengthening the resilience and belief in themselves, these users become confident and back to the place of the protagonists of their own lives.